Persepsi Masyarakat Terhadap Kinerja Pendamping Kampung Ramah Dalam Pemberdayaan Perempuan Dan Perlindungan Anak - Syalsabilah, Nur’aini; Putri, Siska Lusia; Yulyanto, Yulyanto; Surabay, Mitra Msib Batch 5 DP3APPKB Kota (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2025)
This research aims to determine the community's perception of the performance of friendly village assistants in RW 14 Sidoyoso, Simokerto Village, Surabaya. This research is research using a qualitative descriptive method. The results of the research show that the community's perception of the performance of friendly village assistants inRW 14 Sidoyoso, Simokerto Village consists of two perceptions, namely positive perceptions and negative perceptions. The community's positive perception of the companion's performance is that the companion is able to build an attitude of closeness with residents as evidenced by the activities carried out, the companion takes an approach to build an attitude of closeness between residents. Apart from that, the companion also patiently accompanied the respondents, especially mothers who incidentally had an impatient attitude. The companion was consideredcapable of sharing information and knowledge very patiently with the residents. Meanwhile, the community's negative perception of the companion's performance is that there are still several things that need attention and improvement in the future, such as providing explanations regarding activities in the friendly village program, which is considered to be lacking in caution, causing residents to ask forfurther explanations.